Estimasi Sumberdaya Batugamping di PT X, Kecamatan Palimanan, Kabupaten Cirebon, Provinsi Jawa Barat - Dika Hadi Anugrah; Dono Guntoro (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. Limestone is an excavated material that can be used as a raw material for cement. In the manufacture of cement there are three raw materials, namely limestone as the main raw material, then there are corrective raw materials, namely iron sand and quartz sand and additive raw material, namely gypsum. The main compound of limestone used as raw material for cement is CaO compound. In the formation of limestone, the value of CaO content has variations due to differences in facies in the formation process, so that the distribution of CaO content is not necessarily homogeneous. With the requirement for CaO content as a cement raw material, which is 47%, it is necessary to have a model to describe the geometry of the sediment and the distribution of CaO levels at the research site. The resource estimation method used is the kriging method. The basis for determining resources is to talk about the level of confidence. Thus, the selection of the kriging method is because this method is the best linear unbiased estimator, many parameters are considered in the kriging method, one of which is the variogram model. The variogram model is a spatial statistical analysis (geostatistics), or statistical analysis by considering the location of the sample points, in order to obtain information related to the relationship of one point to another which is expressed in a range or radius of information points that still have a spatial relationship. The results of the estimation of limestone resources are as follows. Limestone resources in Quarry B are 12,844,500 tons with an average CaO content of 48.48%, and in Quarry C as many as 10,857,000 tons with an average CaO content of 41.17%. Abstrak. Batugamping merupakan bahan galian yang dapat dimanfaatkan salah satunya sebagai bahan baku semen. Dalam pembuatan semen terdapat tiga bahan baku, yaitu batugamping sebagai bahan baku utama, kemudian terdapat bahan baku corrective yaitu pasir besi dan pasir kuarsa serta bahan baku additive yaitu gypsum. Senyawa utama batugamping yang dimanfaatkan sebagai bahan baku semen adalah senyawa CaO. Pada keterbentukan batugamping, nilai kadar CaO memiliki variasi yang diakibatkan adanya perbedaan fasies dalam proses pembentukannya, sehingga distribusi kadar CaO yang belum tentu homogen. Dengan adanya syarat kadar CaO sebagai bahan baku semen yaitu 47% maka perlu adanya pemodelan untuk menggambarkan bentuk geometri endapan dan distribusi kadar CaO di lokasi penelitian. Metode estimasi sumberdaya yang digunakan adalah metode kriging. Dasar dalam penentuan sumberdaya adalah berbicara terkait tingkat keyakinan. Dengan demikian, pemilihan metode kriging dikarenakan metode ini merupakan best linear unbiased estimator, banyak parameter yang diperhatikan dalam metode kriging salah satunya adalah model variogram. Model variogram merupakan analisis statistik spasial (geostatistik), atau analisis statistik dengan mempertimbangkan lokasi titik sampel, sehingga didapatkan informasi terkait hubungan satu titik dengan titik yang lainnya yang dinyatakan dalam range atau radius titik informasi yang masih memiliki hubungan secara spasial. Hasil dari estimasi sumberdaya batugamping adalah sebagai berikut Sumberdaya batugamping di Quarry B sebanyak 12.844.500 Ton dengan kadar rata-rata CaO 48,48%, dan di Quarry C sebanyak 10.857.000 Ton dengan kadar rata-rata CaO 41,17%.